The impact of fire in Canarian ecosystems 1983 - 1998 - Höllermann, Peter (ERDKUNDE, 2000)
The paper gives a brief report about 15 years of studies in fire-affected ecosystems of the Canary Islands. On the islands of the Province S/C de Tenerife 12 extensive wildfires took place between 1983 and 1998, with a total area of about 24,300 ha of forest and shrubland (Fig. 1). The dominance of light or moderate surface fires, as well as the very effective pyrophytic adaptions of the native flora can explain, that the fire impact and the geoecological consequences following fire were neither detrimental on a large scale nor long lasting. In the forest- and shrubland belt of the central and western Canary Islands fire impact was of geoecological importance at all times, and likewise will be in times to come. The extensive degradation of native Canarian forests and woodlands is not a matter of fire impact, but is due to detrimental land use practices and a heavy wood exploitation in the past. Nevertheless, fire as a menace to human property and lives requires effective measures of fire-fighting and fire management. Namely the recent escalation in the number of fires caused by arson is alarming. Concepts of future fire management are discussed. Experiences transferred from the Iberian Peninsula or from other Mediterranean countries are of restricted use only, because of the different and specific fire-ecological situation on the Canary Islands. The major ecological problem is not the occurrence and impact of fire in Canarian ecosystems in general, but the abuse of fire by man and the extensive human impact on the natural environments of the islands.